Acute effects of combined Bacopa, American ginseng and whole coffee fruit on working memory and cerebral haemodynamic response of the prefrontal cortex: a double-blind, placebo-controlled study. (2nd November 2021) - Best, Talitha; Clarke, Chantelle; Nuzum, Nathan; Teo, Wei-Peng
ABSTRACT: Objective: This study assessed whether a multi-ingredient herbal supplement containing Bacopa monniera (BM), Panax quinquefolius ginseng (PQ) and whole coffee fruit extract (WCFE) could enhance cognitive performance and cerebral-cortical activation during tasks of working memory and attention. Method: In a randomised, double-blind, placebo-controlled, between-group study, 40 healthy adults between 18–60 years ( M = 34.46 SD = 12.95) completed tasks of working memory and attention at baseline and 45 min post active or placebo supplement consumption. During the cognitive testing, changes in hemodynamic response in the prefrontal cortex (PFC) were continuously measured using functional near-infrared spectroscopy (fNIRS). Results: Working memory task performance on the N-back task was significantly improved following active supplement consumption compared to placebo in terms of accuracy ( p < .01) and response time ( p < .05). Improved performance was associated with a reduction of PFC activation ( p < .001) related to effortful mental demand, reflecting increased neural efficiency concomitant with improved cognitive performance. The effects were independent of background demographics variables and changes in blood glucose response and mood. Discussion: This is the first report of acute effects on cognitive performance in healthy adults following intake of a combined, multi-ingredient herbal supplement with concomitant changes in cerebral haemodynamic response. The potential synergistic effects of polyphenolic compounds on neurocognitive function and fNIRS use in nutritional intervention studies, poses a significant increase in the capacity to understand the effects of dietary compounds on the brain.